2002
DOI: 10.1002/1521-3757(20020617)114:12<2203::aid-ange2203>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Totalsynthese von Woodrosin I Diese Arbeit wurde von der Deutschen Forschungsgemeinschaft (Leibniz-Programm) und dem Fonds der Chemischen Industrie unterstützt. Wir danken Professor K. Miyahara, Osaka, Japan, für eine Probe des nahe verwandten Naturstoffs Woodrosin II zu Vergleichszwecken sowie Frau K. Radkowski für ihre wertvolle Mitarbeit in verschiedenen Stadien dieses Projekts.

Abstract: Ein Beleg für die Verlässlichkeit der Ringschlussmetathese selbst in komplexen Fällen ist die Totalsynthese des strukturell anspruchsvollen Harzglycosids Woodrosin I 1. Zugleich zeigt diese Synthese die Reife der Trichloracetimidatmethode, und sie umfasst die wohl anspruchsvollste Anwendung einer Orthoesterumlagerung zur Bildung einer β‐glycosidischen Bindung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(6 citation statements)
references
References 10 publications
0
4
0
2
Order By: Relevance
“…Outlined below is an unambiguous assignment of the stereostructure of glucolipsin A by comparison of the published data with those of all conceivable C 2 -symmetrical dimers of this type. As part of a long-term project on bioactive glycoconjugates, we prepared this set of compounds by a highly integrated synthesis route based on a template-directed cyclodimerization reaction as the key step. In contrast to previous assumptions, however, this study revealed that the fatty acid moiety of glucolipsin A comprises a syn -aldol with a (3 S )-configured stereocenter, opposite the (3 R )-configured motif found in cycloviracin 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Outlined below is an unambiguous assignment of the stereostructure of glucolipsin A by comparison of the published data with those of all conceivable C 2 -symmetrical dimers of this type. As part of a long-term project on bioactive glycoconjugates, we prepared this set of compounds by a highly integrated synthesis route based on a template-directed cyclodimerization reaction as the key step. In contrast to previous assumptions, however, this study revealed that the fatty acid moiety of glucolipsin A comprises a syn -aldol with a (3 S )-configured stereocenter, opposite the (3 R )-configured motif found in cycloviracin 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter the Fürstner group expanded rapidly, initial emphasis being on RCM‐based syntheses of complex natural products, woodrosin I (Scheme )45a and iejimalide45b,c being two of many examples. Parallel to these activities, the catalysts themselves were structurally modified (including fine‐tuning of N ‐heterocyclic carbene ligands) and subsequently used by Fürstner’s co‐workers and by many groups worldwide.…”
Section: Alois Fürstner As Director Of the Department Of Organometmentioning
confidence: 99%
“… Top: Structure of woodrosin I with the indicated site of RCM sufficiently removed from possibly interfering functional groups and the novel indenylidene–ruthenium catalyst developed in the Fürstner group 45a. Bottom: Structure of iejimalide featuring the site of RCM and the catalyst used in the ring‐closing process 45b,c.…”
Section: Alois Fürstner As Director Of the Department Of Organometmentioning
confidence: 99%
“…Hiernach expandierte die Fürstner‐Gruppe rapide, wobei zunächst der Schwerpunkt auf der RCM‐basierten Synthese von Naturstoffen lag. Woodrosin I45a und Iejimalid45b,c seien hier als zwei von vielen Beispielen erwähnt (Schema ). Parallel zu diesen Arbeiten wurden die Katalysatoren selbst strukturell modifiziert (darunter die Feinabstimmung N‐heterocyclischer Carbenliganden) und daraufhin von Fürstners Mitarbeitern und vielen Gruppen weltweit genutzt.…”
Section: Alois Fürstner Als Direktor Der Abteilung Für Metallorganunclassified
“… Oben: Struktur von Woodrosin I mit der angezeigten Stelle für RCM (weit von möglicherweise störenden funktionellen Gruppen) und der neuartige, von der Fürstner‐Gruppe hergestellte Indenyliden‐Ru‐Katalysator 45a. Unten: Struktur von Iejimalid mit der RCM‐Stelle und dem im Ringschlussprozess verwendeten Katalysator 45b,c.…”
Section: Alois Fürstner Als Direktor Der Abteilung Für Metallorganunclassified